Determination of streamflow discharge hydrograph in the Rompin river basin - Yong, Tze Wei (2018)
Generally, the Rompin River Basin is affected by two major water-related problems, floods and droughts. There are two types of floods occur in this country which are the monsoon flood and flash flood. Monsoon floods normally took place at the end of the year during the north-east monsoon. Oppositely, drought occurs during the dry period from May to September causing insufficient water supply especially for irrigation purpose. Thus, it is important to understand the hydrological process involved in the river basins. This study aims to estimate the streamfow for the Rompin River Basin using HEC-HMS hydrological model, and calibrate and validate the transformed rainfall-runoff model. HEC-HMS model is chosen because it is simple to apply and require no licensing. Data of 6 rainfall and 2 streamflow stations in the Rompin River Basin from the year 1990 to 2013 were used in the input, calibration and validation processes. For the surface runoff transformation method, SCS method was selected. In this study, results indicate that the HEC-HMS model is able to simulate the streamflow in the Rompin River Basin with sufficient efficiency for both the dry and wet periods. This finding is important as a decision support tool that can be used in the operation and management of Rompin area, for both water supply and flood control.